Peran Masyarakat dalam Pengembangan Wisata Pulau Putri di Kelurahan Sambau, Nongsa, Kota Batam - Tito Pratama; Dailami .; Rezki Alhamdi; Moh. Thamdzir; Natal Olotua Sipayung; Syafruddin Rais; Siska Amelia Maldin; Wahyudi Ilham; Syalendra Reza Irwansyah Rezeki; Haufi Sukmamedian; Bojes Ariansya; Gita Irmalya (CV. ITTC INDONESIA, 2025)
This study aims to identify and analyze the role of the community in the development of tourism on Putri Island, located in Sambau Village, Nongsa District, Batam City. Community-based tourism development is key to creating a sustainable tourism destination and providing economic, social, and cultural impacts for the local community. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation of local residents, tourism managers, and local government officials. The research results show that communities play a crucial role in tourism development, both as key actors in tourism activities, providers of tourism services and facilities, and guardians of the local environment and culture. However, several obstacles remain, such as limited knowledge of tourism management, minimal promotion, and insufficient government support. Efforts made by communities to address these challenges include raising awareness of the importance of togetherness, tourism skills training, and strengthening collaboration between communities, the government, and the private sector. This study concludes that active community participation is a key factor in the successful development of Putri Island tourism. Therefore, ongoing support from various parties is needed to ensure Putri Island's development into a leading, competitive, and sustainable tourist destination.